SIFAT FISIK DAN KADAR PROKSIMAT SNACK BAR DENGAN PENAMBAHAN WORTEL (DAUCUS CARROTA L) DAN SALAK PONDOH (SALACCA EDULIS REINW) SEBAGAI ALTERNATIF CEMILAN ANAK SEKOLAH - Apriatun Hasanah; Farissa Fatimah; Tri Mei Khasana (Universitas Respati Yogyakarta, 2022)
Physical properties and proximate content of snack bar with addition carrot (daucus carrota l) and snake fruit (salacca edulis reinw) as alternative school children snacksBackground: Elementary school children aged 5-12 years are very vulnerable to nutritional problems because of the increased need for nutrients for optimal growth and development. The prevalence of underweight nutritional status in elementary school children aged 5-12 years is 6.8%. Judging from the proportion of the population aged 5, the level of fruit and vegetable consumption in the lower category is 95.5%. An alternative product development is needed to support the growth and development of school children from local food containing micronutrients, macronutrients, vitamins and minerals, namely by utilizing fruits, vegetables and nuts which are high in nutrients and formulated in the form of snack bars. Objective: This research aimed to assess the effect of variation adding carrot and snake fruit in snack bar on physical properties and proximate content. Methods: This was is true experiment with Completely Randomized Design (CRD) which consistd of 3 treatment adding carrot and snake fruit is 40%:60%, 50%:50%, 60%:40%. This research was conducted in the dietetic and culinary laboratory of Universitas Respati Yogyakarta, the proximate content test in the laboratory of Chemix Pratama Banguntapan Bantul. The data were analyzed by using One Way Anova, if there are differences continued with least significant Different (LSD). Results: The snack bar has a dark brown color in formulation A, brown in formulation B, light brown in formulation C, very sweet taste in formulation A, sweet in formulation B, Slightly sweet in formulation C, smell a peanut butter flavor and soft texture in formulation A, slightly soft texture on formulation B, hard texture on formulation C. Snack bar C have the highest water content (17,28%), ash content (2,72%) and fat content (18,12%). The highest protein content (6,37%) and the highest crude content (24,09%) in Snack bar B. The highest carbohydrate content (42,84%) in snack bar A. Conclusion: There is an effect of adding carrot and snake fruit in making snack bar on physical properties. There is an effect of adding carrot and snake fruit in making snack bar on proximate content.